Fusobacterium nucleatum Affects Cell Apoptosis by Regulating Intestinal Flora and Metabolites to Promote the Development of Colorectal Cancer - Yu, Tingting; Ji, Ling; Lou, Liqin; Ye, Shiqing; Fang, Xiaoting; Li, Chen; Jiang, Feizhao; Gao, Hongchang; Lou, Yongliang; Li, Xiang (Frontiers in Microbiology, 2022)
Background/Aims: Intestinal flora, especially Fusobacterium nucleatum (Fn), can affect the development of colorectal cancer (CRC). In this study, we examined the composition of intestinal flora and metabolites in the tissues, serum and feces of CRC patients. Materials and Methods: CRC tissues, adjacent normal colonic tissues, and fecal and serum samples were collected from CRC patients who received surgical treatment between January 2018 and January 2020. Fecal and serum samples were collected from healthy individuals for comparison. In addition, fecal samples were collected from BALB/c female mice. SW480, a human CRC cell line, was utilized for in vitro studies. Results: The abundance of Bacteroides and propionic acid concentration were decreased. The abundance of Lactobacillus and lactic acid concentration were increased in CRC tissues. KEGG pathway analysis showed that Bacteroides and Lactobacillus were related to the apoptotic pathway. Additionally, lactic acid inhibited and propionic acid promoted apoptosis among SW480 CRC cells. Similar findings were noted in the feces of Fn gavage mice. In addition, the abundances of Ruminococcus, Prevotella, and Sutterell were decreased in CRC patients. The levels of leucine and isoleucine were decreased in the serum and tumor tissues of CRC patients. Aspartate, glutamate and glutathione levels were elevated in the tissues of CRC patients only. The serum glutamine, tyrosine, valine, alanine, and histidine levels were decreased significantly. Conclusions: Fn affected the apoptosis of CRC cells and promoted the progression of CRC by affecting the distribution of intestinal flora, which altered the concentrations of metabolites such as lactic acid, propionic acid, and amino acids.